The forest and the fort - Allen, Hervey, 1889-1949. (New York : Rinehart & Company, 1943)
Salathiel Albine, a white child who has lived with the Shawnee Indians from a young age chooses to reidentify with his white parentage after spending some time with a preacher who helps him relearn English. Story points up to cultural differences which made Indian-White conflict inevitable as settlers pressed westward.
Keywords: American fiction